Energy Efficiency Increase by Improved Heat Storage in Wood Stoves - Oyvind Skreiberg; Morten Seljeskog (Chemical Engineering Transactions)
Wood stoves are widely used for space heating in cold climates and provides energy security and relieves the pressure on the electricity grid, especially on cold winter days. In this work the influence of heat storage capacity on the stove thermal efficiency is investigated to explain the experimentally observed influence of heat storage capacity on stove thermal efficiency. A high heat storage capacity as for soapstone stoves typically gives several percentage points increase in stove thermal efficiency compared to cast iron or plate steel stoves. The heat storage provides a possibility for the heat to be temporarily stored instead of being transported out of the stove with the flue gas, and counteracts the main heat transfer resistance, the transfer of heat to the room from the outer stove surface. However, as the heat storage capacity increases, so do the amount of heat that could be lost to air leaking through the stove after the firing ends. For stove materials, their thermal inertia and mass are crucial for the heat storage capacity, while the transfer of the heat is also controlled by the heat transfer through the material. As a result, soapstone has a benefit with respect to thermal comfort, while cast iron for thermal efficiency, for an equal heat storage capacity. However, soapstone stoves have much higher heat storage capacity than cast iron stoves, and therefore also achieve the highest thermal efficiencies in type approval tests.